2018
DOI: 10.1615/plasmamed.2018028261
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Differences Between Antimicrobial and Cytotoxic Properties of Plasma Activated Liquids

Abstract: Retention of plasma reactive species to liquids is a promising new technology, an alterna-5-11 and also as a new eco-friendly 12 13 Building an understanding of a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
24
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 0 publications
5
24
0
Order By: Relevance
“…2c). Comparing with previous results 32 , CAP treatment of culture media for 30 s generated very low amounts of H 2 O 2 (~20 μM), NO 2− (~5 μM), and NO 3− (~30 μM) which are at least 15-fold and 200-fold lower than the IC 50 cytotoxicity values we measured previously for U373MG cells (315 µM, >1200 µM and >600 µM respectively) and therefore are essentially non-toxic 33 www.nature.com/scientificreports www.nature.com/scientificreports/ CAP treatment when measured using H 2 DCFDA by flow cytometry (Fig. 2d).…”
Section: Resultssupporting
confidence: 56%
“…2c). Comparing with previous results 32 , CAP treatment of culture media for 30 s generated very low amounts of H 2 O 2 (~20 μM), NO 2− (~5 μM), and NO 3− (~30 μM) which are at least 15-fold and 200-fold lower than the IC 50 cytotoxicity values we measured previously for U373MG cells (315 µM, >1200 µM and >600 µM respectively) and therefore are essentially non-toxic 33 www.nature.com/scientificreports www.nature.com/scientificreports/ CAP treatment when measured using H 2 DCFDA by flow cytometry (Fig. 2d).…”
Section: Resultssupporting
confidence: 56%
“…As seen in Figure 2c, the RONS generated in CAP-treated phenol red-free medium are presented after normalising to the values of untreated medium. By direct comparison previous results 38 , CAP treatment of culture media for 30 s generated very low amounts of H2O2 (~20 μM), NO 2-(~5 μM), and NO 3-(~30 μM). These concentrations are at least 15-fold and 200-fold lower than the IC50 values we measured previously for U373MG cells (315 µM, >1200 µM and >600 µM respectively) and therefore are essentially non-toxic 39 .…”
Section: Numerical Modelling Of the Uptake Of Aunps By Gbm Cellssupporting
confidence: 61%
“…The generated RONS in the CAP-treated culture medium, including hydrogen peroxide, nitrite and nitrate, were also quantitatively measured (As seen in Figure 2c). By comparison with our previous study 38,42 , after the same low does CAP treatment (30 s, 75 kV), the levels of generated H2O2, NO -2, and NO -3 in culture medium are relatively low cytotoxic to U373MG cells, but still are able to induce lipid peroxidation.…”
Section: Discussionsupporting
confidence: 46%
“…Baik et al. (2013) and Tsoukou, Bourke, and Boehm (2018) also did not obtain any inactivation or acidification for PBS after plasma treatment. Oehmigen et al.…”
Section: Factors Influencing the Inactivation Efficiency Of Pawmentioning
confidence: 93%
“…The results showed that 5 log reduction of E. coli was achieved after 15 min exposure with PAW, whereas no reduction was observed for PAPBS, and the pH remained 7 after plasma treatment. Baik et al (2013) and Tsoukou, Bourke, and Boehm (2018) also did not obtain any inactivation or acidification for PBS after plasma treatment. Oehmigen et al (2010) investigated the inactivation activity of saline and PBS against E. coli after plasma treatment of 0 to 30 min in three volumes of 1.5, 5.0, and 10.0 mL, and inactivation was observed in nonbuffered solution of all the volumes.…”
Section: Background Environment Of Watermentioning
confidence: 97%